Implementing essential diagnostics-learning from essential medicines: A scoping review. - Moriasi Nyanchoka; Mercy Mulaku; Bruce Nyagol; Eddy Johnson Owino; Simon Kariuki; Eleanor Ochodo (PLOS Global Public Health)
The World Health Organization (WHO) model list of Essential In vitro Diagnostic (EDL) introduced in 2018 complements the established Essential Medicines List (EML) and improves its impact on advancing universal health coverage and better health outcomes. We conducted a scoping review of the literature on implementing the WHO essential lists in Africa to inform the implementation of the recently introduced EDL. We searched eight electronic databases for studies reporting on implementing the WHO EDL and EML in Africa. Two authors independently conducted study selection and data extraction, with disagreements resolved through discussion. We used the Supporting the Use of Research Evidence (SURE) framework to extract themes and synthesised findings using thematic content analysis. We used the Mixed Method Appraisal Tool (MMAT) version 2018 to assess the quality of included studies. We included 172 studies reporting on EDL and EML after screening 3,813 articles titles and abstracts and 1,545 full-text papers. Most (75%, n = 129) studies were purely quantitative in design, comprising descriptive cross-sectional designs (60%, n = 104), 15% (n = 26) were purely qualitative, and 10% (n = 17) had mixed-methods approaches. There were no qualitative or randomised experimental studies about EDL. The main barrier facing the EML and EDL was poorly equipped health facilities-including unavailability or stock-outs of essential in vitro diagnostics and medicines. Financial and non-financial incentives to health facilities and workers were key enablers in implementing the EML; however, their impact differed from one context to another. Only fifty-six (33%) of the included studies were of high quality. Poorly equipped and stocked health facilities remain an implementation barrier to essential diagnostics and medicines. Health system interventions such as financial and non-financial incentives to improve their availability can be applied in different contexts. More implementation study designs, such as experimental and qualitative studies, are required to evaluate the effectiveness of essential lists.